Estimation of genetic variability, heritability and correlation for some quantitative traits in wheat (Triticum aestivum L.) (Journal of Bio-Science, 2019)
Seventeen genotypes of wheat were used in this study the results showed significant differences in respect of yield and other yield contributing characters. Highest phenotypic and genotypic coefficients of variations were observed in plant height and lowest values were observed in spike length in both cases.Heritability estimated was found to be high in case of grain yield/plant and this was followed by 100 grain weight. Significant positive correlation was found in plant height with number of fertile tillers/plant and grain yield/plant, fertile tillers/plant with spike length, spike length with grain yield and grain yield with 100 grain weight. Negative correlation was found in plant height with 100 grain weight. Plant height, fertile tillers/plant, spike length and 100 grain weight appeared to be the effective criteria for improvement of yield of wheat.J. bio-sci. 28: 81-86, 2020